Images and representations of menopause in a Malaysian woman magazine: an analysis of MIDI - Sedu, Nerawi; Mohamad Diah, Nurazzura (Canadian Center of Science and Education, 2015)
Magazine is one of the main sources of information on health-related issues, including menopause. Due to its format and writing style, a magazine can be regarded as an easy reading. Considered to be a taboo or non-spoken topic in some societies, menopause does not receive similar amount of coverage by the magazines as compared to business, education, beauty and fashion. In other words, it is regarded as less important women issues. The study aims to analyse the images or representations of menopause in a woman magazine. Compared to other studies on the portrayals of women and women-related issues in the mass media, this study only focuses on depictions of menopause in MIDI. The magazine is a fortnightly Malay language publication specifically targeted at female readers aged forty and above. The data for this study were gathered for several months in years 2006, 2007, 2008, and 2009. The articles from MIDI were analysed using thematic analysis, focusing on the concepts or expressions or phrases used by the magazine to depict the concept of menopause. The findings of the study highlighted some of the common images and representations of menopause in MIDI.